PEREMPUAN DAN EKSPLOITASI - FATMAWATI FATMAWATI (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2014)
The existence of mass media that dominated by western has abig influence to spread the exploitation idea, especially to islamic country. Politicly, the western has willing to demage the muslim society with idea and culture war as replacing the physic war. The exploitation ideas has been recieved by muslimah and becomean instrumental to spread the idea in the society. The muslimah effort to exist in the world become without the religious norm. Sometimes they go aut from their house a porbidden purpose by religious thought and open the part of the body wich may not be visible by other, free sexual intercourse. Ironicly, this attitudes become a new life styale, and the religious thought was regarded as limitation to their life style.Now can be found muslimah in television station, advertising, commercialization of publications, and they are become the popular idol of today’s modern muslimah.For the problem, islamic thought give best solution. Only back to Alquran and hadis can minimize the women axploitation. Alquran give guidence for muslimah to cover the part of body wich may not be visible by other and select the culture can accept ang suitable with islmic thought. From this, muslimash have to be given islamic thought orientation to increase their faith until they can free from the exploitation activity.